Appearance of the endometrium at saline contrast sonohysterography in the luteal phase of the menstrual cycle: a prospective observational study. (28th January 2015) - Jokubkiene, L.; Sladkevicius, P.; Valentin, L.
ABSTRACT: Objective: To describe the ultrasonographic morphology of the endometrium at saline contrast sonohysterography (SCSH) performed in the luteal phase of the menstrual cycle in women 20–38 years of age with regular menstrual cycles. Methods: The study included 26 women (median age 33 (range, 20–38) years) with regular menstrual cycles referred for hysterosalpingo‐contrast sonography (HyCoSy) as part of infertility work‐up ( n  = 19) or before donor insemination in lesbian couples ( n  = 7). SCSH and HyCoSy were performed 6–10 days after a positive luteinizing hormone (LH) urinary self‐test. Three‐dimensional (3D) ultrasound volumes of the uterus were saved with and without saline in the uterine cavity. The results presented are based on offline analysis of the 3D volumes. Results: Median endometrial thickness was 10.4 (range, 6.0–17.3) mm. Twelve (46%; 95% CI, 27–65%) of the 26 women had endometrial folds at SCSH. The number of folds varied between 1 and 6 (median 3). Endometrial thickness was similar in women with and without endometrial folds (median endometrial thickness 10.7 (range, 6.0–17.3) mm vs 10.1 (range, 6.1–14.4) mm; P  = 0.257), and the amount of saline in the uterine cavity did not differ between the two groups (median 8.6 (range, 5.2–12.9) mm vs 7.1 (range, 3.2–13.3) mm; P  = 0.527). In two women with endometrial folds at two‐dimensional (2D) or 3D‐SCSH, focal endometrial pathology (polyp) was suspected, but hysteroscopically resected endometrium showed normal histology. Conclusions: One should avoid performing SCSH in the luteal phase of the menstrual cycle, not only because there may be a fertilized ovum in the genital tract but also because endometrial folds are common in this phase and may lead to overdiagnosis of focal endometrial pathology, such as polyps. If, for some reason, SCSH is performed in the luteal phase and the results are equivocal, the procedure should be repeated in the follicular phase. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.